Investigating the effect of nonionic surfactant on the silica nanoparticles formation and morphology in a microfluidic reactor - Fiona Ling, Wang Ming; Abdulbari, Hayder A.; Chin, S. Y. (Springer, 2021)
The conventional sol-gel method used to synthesize monodispersed spherical silica nanoparticles produces particles with irregular shapes and low monodispersity. Microreactors show a promising new platform to synthesize nanomaterials due to their unique flow and mixing characteristics. In most known shear-based droplet generation microreactors, the effect of the flowing liquid’s physical properties on the reactor performance and product characteristics are not well investigated. Scaling-down the flow system was proven to change the flow behavior which will be dominated by the liquid apparent physical properties that are highly controllable. A new method to synthesize silica nanoparticles adapting the sol-gel approach in a microfluidic chip is proposed and experimentally tested in the present work. This work also analyzes changing the flowing reactants’ physical properties using nonionic surfactants with different concentrations on the reaction performance and nanoparticle size and properties. A custom-made microreactor, made from polydimethylsiloxane, was designed and then fabricated using a direct writing technique. The investigated surfactant concentration was within the range of 1 to 5 vol/vol%, respective to tetraethyl orthosilicate. A traditional bench-scale sole-gel method was also performed with the same reaction properties for comparison purposes. The obtained nanoparticles were characterized using transmission electron microscopy and EDX. The silica nanoparticles synthesized from a bench-scale system showed poor monodispersity and an irregular shape compared to the perfect spherical particles produced from the microflow system. The addition of surfactant reduced the coalescence of the droplet besides reducing the size of the droplets. Increasing the surfactant concentration reduces the silica nanoparticle size. The results showed that highly monodispersed silica nanoparticles with an average size of 5.76 ± 1.27 nm were synthesized using the microflow system comparing to silica nanoparticles with a mean size of 95 ± 4 nm produced from the bench-scale.